Boosting Corporate Value through ESG Excellence in Oil and Gas Sector - Dsouza, Suzan; Krishnamoorthy, K. (International Journal of Energy Economics and Policy, 2024)
The research investigates the impact of Environmental, Social, and Governance (ESG) excellence on the corporate valuation in the oil and gas sector, addressing the problem of quantifying ESG’s influence on market worth. The study utilized a comprehensive dataset from the Thomson Reuters database, covering 960 global firms over the period 2011-2022. Through empirical analysis, the study revealed that while ESG excellence directly correlates negatively with corporate valuation, its indirect benefits through enhanced profitability and operational efficiency are significant. Specifically, ESG excellence improves operational efficiency, which in turn positively impacts market value. The study found no direct significant impact of ESG excellence on profitability, but enhanced operational efficiency mediated by ESG leads to increased corporate valuation. These findings highlight the importance of converting ESG efforts into tangible financial benefits, emphasizing profitability and operational efficiency as key mediators. The study concludes that ESG practices, when effectively integrated into business strategies, significantly enhance a firm’s market value and operational efficiency. This research provides actionable insights for policymakers, corporate strategists, and investors, promoting the adoption of robust ESG practices to achieve sustainable growth and long-term financial success in the oil and gas sector. Future research should focus on industry-specific analyses, longitudinal studies, and the development of sophisticated ESG metrics to further elucidate these relationships.